2019
DOI: 10.1186/s12885-019-6150-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between immune-related adverse events and prognosis in patients with gastric cancer treated with nivolumab

Abstract: BackgroundRecent studies have shown that immune-related adverse events (irAEs) caused by immune checkpoint inhibitors were associated with clinical benefit in patients with melanoma or lung cancer. In advanced gastric cancer (AGC) patients, there have been few reports about the correlation between irAEs and efficacy of immune checkpoint inhibitors. In this study, we retrospectively investigated the correlation between irAEs and efficacy in AGC patients treated with nivolumab.MethodsThe subjects of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 37 publications
7
51
0
2
Order By: Relevance
“…Previous studies have shown that immunerelated events occurring early in the course of immune checkpoint inhibitor treatment may correlate with clinical benefit in several malignancies. [14][15][16][17] No new safety signals were observed, and the overall incidence of treatment-related events with longer follow-up was similar to previous rates. 3 8 Looking at treatmentrelated AEs by 6-month interval, the overall incidence decreased over time in both arms, yet consistently higher rates of any-grade and grade 3-4 AEs occurred with SUN versus NIVO+IPI.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown that immunerelated events occurring early in the course of immune checkpoint inhibitor treatment may correlate with clinical benefit in several malignancies. [14][15][16][17] No new safety signals were observed, and the overall incidence of treatment-related events with longer follow-up was similar to previous rates. 3 8 Looking at treatmentrelated AEs by 6-month interval, the overall incidence decreased over time in both arms, yet consistently higher rates of any-grade and grade 3-4 AEs occurred with SUN versus NIVO+IPI.…”
Section: Discussionsupporting
confidence: 78%
“…A retrospective study focusing on patients with advanced gastric cancer treated with nivolumab (n=65) conducted by Masuda et al found significantly longer PFS and OS in patients with irAEs compared to those without (p<0.001 and p<0.001, respectively) (45). Furthermore, the results of multivariable Cox model demonstrated that absence of irAEs represented an independent factor associated with a poor prognosis (HR=9.54, p<0.001) (45).…”
Section: Iraes and Outcome In Other Malignanciesmentioning
confidence: 99%
“…Second, although examinations for PD-L1 expression, MSI or Epstein-Barr virus positivity require technical expertise, GPS and DCBC do not. Finally, with the use of GPS and DCBC, prediction can be made prior to administration of nivolumab, unlike previously suggested biomarkers such as development of immune-related adverse events (25). On the other hand, the following disadvantages should be taken into account: GPS is intrinsically susceptible to transient inflammation including acute infection, and DCBC can be utilized only when the information of response to chemotherapy immediately prior to nivolumab is available.…”
Section: Discussionmentioning
confidence: 99%